2019
DOI: 10.3390/md17010042
|View full text |Cite
|
Sign up to set email alerts
|

The Neglected Marine Fungi, Sensu stricto, and Their Isolation for Natural Products’ Discovery

Abstract: Despite the rapid development of molecular techniques relevant for natural product research, culture isolates remain the primary source from which natural products chemists discover and obtain new molecules from microbial sources. Techniques for obtaining and identifying microbial isolates (such as filamentous fungi) are thus of crucial importance for a successful natural products’ discovery program. This review is presented as a “best-practices guide” to the collection and isolation of marine fungi for natura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
41
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 71 publications
1
41
0
Order By: Relevance
“…The importance of fungi as a new source of bioactive compounds was first focused by the discovery of penicillin from Penicillium notatum in 1928 by Alexander Flemming. A molecular study reported that fungal communities differ between marine lives collected at the same site and also differ from those present in the surrounding marine water [18][19][20] . Up to 2016, nearly 600 new compounds were reported from marinederived symbiotic microorganisms of which over 70% were obtained from epi/endophytes derived from marine weeds, invertebrates and woody substrates 21 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of fungi as a new source of bioactive compounds was first focused by the discovery of penicillin from Penicillium notatum in 1928 by Alexander Flemming. A molecular study reported that fungal communities differ between marine lives collected at the same site and also differ from those present in the surrounding marine water [18][19][20] . Up to 2016, nearly 600 new compounds were reported from marinederived symbiotic microorganisms of which over 70% were obtained from epi/endophytes derived from marine weeds, invertebrates and woody substrates 21 .…”
Section: Discussionmentioning
confidence: 99%
“…is able to produce novel anti-bacterial compounds like cyclodepsipeptide enniatin B37, sesterterpenoid neomangicols 22,37 , bromomethylchlamydosporols A38 and antifungal compound, fusarielin E37. So, it can be assumed that the investigated marine fungi can produce antimicrobial secondary metabolites like pest alone due to bacterial competition against other micro-organisms in the marine environment developed through its chemical defense mechanisms 20 . Thus, the five isolates derived from four marine weeds are presumed to be good antibiotic-producer candidates.…”
Section: Discussionmentioning
confidence: 99%
“…The challenging question of the isolation of marine fungi sensu stricto is key to the future exploration of the chemical diversity of marine fungi, and possibly the exploitation of their secondary metabolites. A best-practice guide for the isolation of marine fungi from different matrixes and their conservation is presented by Overy et al [11]. Generalist, osmotolerant/halotolerant genera such as Aspergillus and Penicillium are highly cited in the literature but taxonomic groups composed predominantly of marine fungi sensu stricto such as Halosphaeriaceae, Torpedosporales, and Lulworthiales have been little studied for now.…”
mentioning
confidence: 99%
“…The fungus Geosmithia pallida FS140 was isolated from a sediment collected at 2403 m depth in the South China Sea [14]. Twelve diketopiperazines, including the three new thiodiketopiperazines geospallins A-C (6-8), were isolated from this fungus (Figure 1 In the sea, many fungal species are associated with macroscopic organisms [9,11,15]. The isolation of marine fungi from macroorganisms' tissues may in fact be a fairly straightforward way of isolating marine fungi sensu stricto.…”
mentioning
confidence: 99%
See 1 more Smart Citation